Per3 expression in different tissues of Cebus apella - Sabino, Flávia Cal; De Oliveira, José Américo [UNESP]; Pedrazzoli, Mario (Thieme, 2016)
We present a study of Per3 expression in six different tissues of the non-human primate Cebus apella (capuchin monkey). The aim of this study was to verify whether the expression of the Per3 gene in different tissues of capuchin monkey occurs in a circadian pattern, its phase and the phase relationships between these different tissues during the 24 h of a day. We observed that gene expression oscillated in all of the tissues studied during this time period, although only the liver and muscle presented a robust circadian pattern. This preliminary study highlights the possibility of using Cebus apella as a model to study circadian rhythms at the gene expression level and opens an opportunity for future researches.
Keywords: Capuchin monkey; Circadian expression; Circadian rhythms; Per3 gene; Primate